Long‐term safety of proton pump inhibitor therapy assessed under controlled, randomised clinical trial conditions: data from the SOPRAN and LOTUS studies. Issue 11 (10th April 2015) - Attwood, S. E.; Ell, C.; Galmiche, J. P.; Fiocca, R.; Hatlebakk, J. G.; Hasselgren, B.; Långström, G.; Jahreskog, M.; Eklund, S.; Lind, T.; Lundell, L.
Summary Background Control of chronic gastro‐oesophageal reflux disease may be achieved either by anti‐reflux surgery (ARS) or by long‐term medical therapy with proton pump inhibitors (PPIs). The primary efficacy results of the SOPRAN study, comparing long‐term omeprazole use with open ARS, and the LOTUS study, comparing long‐term esomeprazole use with laparoscopic ARS, have been reported. A secondary objective of these studies was to address the long‐term safety of these respective therapeutic strategies and thereby provide a valid scientific platform for assessing long‐term PPI safety. Aim To assess the safety of long‐term PPI therapy with omeprazole and esomeprazole through analyses of data from the randomised SOPRAN and LOTUS studies. Methods Safety data were collected from patients during the 12‐year period of the SOPRAN study (n = 298) and the 5‐year period of the LOTUS study (n = 514). Reported serious adverse events (SAEs) and changes in laboratory variables were analysed. Results Across both studies, SAEs were reported at a similar frequency in the PPI and ARS treatment groups. Taking the time frames into consideration, the number of fatal SAEs in the two studies was low in both treatment groups. Laboratory results, including routine haematology and tests for liver enzymes, electrolytes, vitamin D, vitamin B12, folate and homocysteine, showed no clinically relevant changes over time. As expected, gastrin and chromogranin A were elevated in the PPI groups, with the greatest increases observed in the first year. Conclusion No major safety concerns arose during 5–12 years of continuous PPI therapy. (ClinicalTrials.gov: NCT00251927 and NCT00256737).